2010
DOI: 10.1021/ja9106176
|View full text |Cite
|
Sign up to set email alerts
|

What Factors Influence the Rate Constant of Substrate Epoxidation by Compound I of Cytochrome P450 and Analogous Iron(IV)-Oxo Oxidants?

Abstract: The cytochromes P450 are a versatile range of mono-oxygenase enzymes that catalyze a variety of different chemical reactions, of which the key reactions include aliphatic hydroxylation and C=C double bond epoxidation. To establish the fundamental factors that govern substrate epoxidation by these enzymes we have done a systematic density functional theory study on substrate epoxidation by the active species of P450 enzymes, namely the iron(IV)-oxo porphyrin cation radical oxidant or Compound I. We show here, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
167
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 164 publications
(192 citation statements)
references
References 113 publications
25
167
0
Order By: Relevance
“…Consistent with the results of the previous DFT studies, 8,49,50 In SOSP1 the Fe-O1 bond is elongated to 2.01 from 1.67Å, whereas the O1-C1 and O1-C2 distances are rather short, i.e. 2.02 and 1.85Å, respectively ( (Fig.…”
Section: Formation Of the Epoxide Intermediate Direct Formation Of Epsupporting
confidence: 90%
“…Consistent with the results of the previous DFT studies, 8,49,50 In SOSP1 the Fe-O1 bond is elongated to 2.01 from 1.67Å, whereas the O1-C1 and O1-C2 distances are rather short, i.e. 2.02 and 1.85Å, respectively ( (Fig.…”
Section: Formation Of the Epoxide Intermediate Direct Formation Of Epsupporting
confidence: 90%
“…Naphthalene ionization energies were computed for both PaDa-I and JaWa variants. Results show that the increase in the substrate's positive electrostatic environment increases naphthalene's ionization energy (from 213.55 kcal/mol in PaDa-I to 214.57 kcal/mol in JaWa), leading to a higher activation barrier, as shown in previous studies [30,31] and in agreement with JaWa lower kcat observed experimentally. On the other hand, The R257K mutation was not expected to affect the hydroxylation of naphthalene but further PELE simulations with DMP show an additional access to the active heme site, close to this residue (not present in naphthalene), which could affect both the Km and kcat.…”
Section: Computational Analysissupporting
confidence: 88%
“…These diagrams have been used previously to rationalize barrier heights of chemical reactions and explain what features of substrate and oxidant affect the value of the barrier height. [21,27] The diagram starts on the bottom-left with the reactant configuration of [Fe IV (O)(Por +• )] + and arene. Thus, in the ground state the system has three unpaired electrons distributed over the *xz, *yz and a1u molecular orbitals.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, the axial cysteinate ligand in P450 enzymes affects the reactivity properties of the oxo group and, thereby makes it a better oxidant. Electrophilic reactions, such as aromatic hydroxylation and epoxidation, however, tend to connect with the ionization energy of the substrate and the electron affinity of the oxidant, [21] which is appropriate for [Fe IV (O)(Por +• )] + to perform these reactions.…”
Section: Theorymentioning
confidence: 99%